2009
DOI: 10.1055/s-0029-1211935
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Graves disease in childhood and adolescence

Abstract: Children and adolescents with thyroid disorders are predominantly treated by pediatricians and pediatric endocrinologists. Surgery for thyroid disorders still represents the third frequent operation in adults in Germany, but is seldomly indicated in children. Thus children and adolescents make up for 1.3% of all our patients and of these 89 patients only 21 (23.6%) suffered from Graves disease. Nevertheless surgery for Graves disease in children and adolescence is recommended because medical therapy has proven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The risk of radioiodine in children is not clear and is generally avoided at our institution for children under the age of 16. Additionally, higher failure rates of antithyroid medication in children often necessitate surgical treatment (10).…”
Section: Discussionmentioning
confidence: 99%
“…The risk of radioiodine in children is not clear and is generally avoided at our institution for children under the age of 16. Additionally, higher failure rates of antithyroid medication in children often necessitate surgical treatment (10).…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Cohen et al [23], surgery was performed by a low-volume surgeon. The remaining 13 studies did not report whether thyroidectomies were performed by a low- or a high-volume surgeon [12, 16-20, 22, 24-26, 28, 30]. In 3 studies, thyroidectomies were performed by a pediatric surgeon [14, 21, 22], in 3 studies by an endocrine surgeon [11, 26, 29], and in 4 by both pediatric and adult surgeons [12, 18, 19, 31].…”
Section: Resultsmentioning
confidence: 99%
“…Sugino et al [26] reported all patients to be euthyroid at the time of surgery, without reporting the used preoperative treatment protocol. The other included studies did not report on preoperative preparation or preoperative thyroid hormone levels in their patients [10, 13, 15, 17-22, 24, 25, 28-31]. Further characteristics of the included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations